Environmental Enrichment Modified Epigenetic Mechanisms in SAMP8 Mouse Hippocampus by Reducing Oxidative Stress and Inflammaging and Achieving Neuroprotection - Griñan-Ferré, Christian; Puigoriol-Illamola, Dolors; Palomera-Ávalos, Verónica; Pérez-Cáceres, David; Companys-Alemany, Júlia; Camins, Antonio; Ortuño-Sahagún, Daniel; Rodrigo, M. Teresa; Pallàs, Mercè (Frontiers in Aging Neuroscience, 2016)
With the increase in life expectancy, aging and age-related cognitive impairments are becoming one of the most important issues for human health. At the same time, it has been shown that epigenetic mechanisms are emerging as universally important factors in life expectancy. The Senescence Accelerated Mouse P8 (SAMP8) strain exhibits age-related deterioration evidenced in learning and memory abilities and is a useful model of neurodegenerative disease. In SAMP8, Environmental Enrichment (EE) increased DNA-methylation levels (5-mC) and reduced hydroxymethylation levels (5-hmC), as well as increased histone H3 and H4 acetylation levels. Likewise, we found changes in the hippocampal gene expression of some chromatin-modifying enzyme genes, such as Dnmt3b, Hdac1, Hdac2, Sirt2, and Sirt6. Subsequently, we assessed the effects of EE on neuroprotection-related transcription factors, such as the Nuclear regulatory factor 2 (Nrf2)–Antioxidant Response Element (ARE) pathway and Nuclear Factor kappa Beta (NF-kΒ), which play critical roles in inflammation. We found that EE produces an increased expression of antioxidant genes, such as Hmox1, Aox1, and Cox2, and reduced the expression of inflammatory genes such as IL-6 and Cxcl10, all of this within the epigenetic context modified by EE. In conclusion, EE prevents epigenetic changes that promote or drive oxidative stress and inflammaging.